Phenotypic analysis of lymphocytes and monocytes/macrophages in peripheral blood and bronchoalveolar lavage fluid from patients with pulmonary sarcoidosis. Issue 4 (1st April 1999) - Wahlström, J; Berlin, M; Sköld, C M; Wigzell, H; Eklund, A; Grunewald, J
Abstract : BACKGROUND: The granulomatous inflammation in sarcoidosis is driven by the interplay between T cells and macrophages. To gain a better understanding of this process the expression by these cells of cell surface activation markers, co-stimulatory molecules, and adhesion molecules was analysed. METHODS: CD4+ and CD8+ T lymphocytes from peripheral blood (PBL) or bronchoalveolar lavage (BAL) fluid, as well as paired peripheral blood monocytes and alveolar macrophages from 27 patients with sarcoidosis were analysed by flow cytometry. RESULTS: CD26, CD54, CD69, CD95, and gp240 were all overexpressed in T cells from BAL fluid compared with those from PBL in both the CD4+ and CD8+ subsets, while CD57 was overexpressed only in BAL CD4+ cells. In contrast, CD28 tended to be underexpressed in the BAL T cells. Monocyte/macrophage markers included CD11a, CD11b, CD11c, CD14, CD16, CD54, CD71, CD80 and CD86 and HLA class II. CD11a expression in alveolar macrophages (and peripheral blood monocytes) was increased in patients with active disease and correlated positively with the percentage of BAL lymphocytes. Expression of CD80 in macrophages correlated with the BAL CD4/CD8 ratio. CONCLUSIONS: Our data indicate substantial activation of both CD4+ and CD8+ lung T cells in sarcoidosis. There were also increased numbers of BAL lymphocytes whose phenotypic characteristics have earlier been associated with clonally expanded, replicatively senescent cells of the Th1 type.